Brassinosteroids Affect the Symbiosis Between the AM Fungus Rhizoglomus irregularis and Solanaceous Host Plants - von Sivers, Lea; Jaspar, Hannah; Johst, Bettina; Roese, Michael; Bitterlich, Michael; Franken, Philipp; Kühn, Christina (Frontiers in Plant Science, 2019)
Together with several proteins involved in brassinosteroid (BR) signaling and synthesis, the membrane steroid binding protein 1 (MSBP1) was identified within the interactome of the sucrose transporter of tomato (SlSUT2). We asked whether MSBP1 is also involved in BR signaling as assumed for the AtMSBP1 protein from Arabidopsis and whether it impacts root colonization with arbuscular mycorrhizal (AM) fungi in a similar way as shown previously for SlSUT2. In addition, we asked whether brassinosteroids per se affect efficiency of root colonization by AM fungi. We carried out a set of experiments with transgenic tobacco plants with increased and decreased MSBP1 expression levels. We investigated the plant and the mycorrhizal phenotype of these transgenic plants and tested the involvement of MSBP1 in BR metabolism by application of epi-brassinolide and brassinazole, an inhibitor of BR biosynthesis. We show that the phenotype of the transgenic tobacco plants with increased or reduced MSBP1 expression is consistent with an inhibitory role of MSBP1 in BR signaling. MSBP1 overexpression could be mimicked by brassinazole treatment. Interestingly, manipulation of MSBP1 expression in transgenic tobacco plants not only affected plant growth and development, but also the host plant responses towards colonization with AM fungi, as well as arbuscular architecture. Moreover, we observed that brassinosteroids indeed have a direct impact on the nutrient exchange in AM symbiosis and on the biomass production of colonized host plants. Furthermore, arbuscular morphology is affected by changes in MSBP1 expression and brassinolide or brassinazole treatments. We conclude that host plant growth responses and nutrient exchange within the symbiosis with AM fungi is controlled by brassinosteroids and might be impeded by the MSBP1 protein.